Graphitization induced by KOH etching for the fabrication of hierarchical porous graphitic carbon sheets for high performance supercapacitors. Issue 29 (6th July 2018) - Qi, Fulai; Xia, Zhangxun; Sun, Ruili; Sun, Xuejing; Xu, Xinlong; Wei, Wei; Wang, Suli; Sun, Gongquan
Abstract : Porous graphitic carbons are promising candidates for energy conversion and storage. Abstract : Porous graphitic carbons are promising candidates for energy conversion and storage. At present, it is highly desired but remains challenging to construct high-surface-area hierarchical porous graphitic carbons. Herein, graphitic carbon nanosheets with hierarchical pores are easily fabricated from a multifunctional carbonaceous precursor (pentaerythritol melamine phosphate or PMP). The PMP carbonaceous precursor can be readily converted into a 3D macroporous scaffold enclosed by carbon nanosheets via chemical foaming without any sacrificial templates and special drying procedures. Then a subsequent potassium hydroxide chemical activation process dramatically increases the surface area (up to 3853 m 2 g −1 ) and porosity (up to 2.79 cm 3 g −1 ). Simultaneously, graphitization of the carbon nanosheets was promoted with increased aromaticity and size of the polyaromatic units via breaking the phosphate ester bonds with KOH etching at a temperature as low as 800 °C. The resulting porous graphitic carbon nanosheets are constructed with an interconnected continuous three-dimensional network surrounded by predominantly multilayer sp 2 -bonded carbon with a dense nanometer scale pore structure. Due to such synergistic features, the resulting porous graphitic carbon nanosheets deliver 188 F g −1 specific capacitance and excellent rate performance in nonaqueous electrolytes.